PENGARUH STRUKTUR MODAL DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PADA SUB SEKTOR BASIC MATERIALS YANG TERDAFTAR DI BEI TAHUN 2019-2023 - Deya Febiola; Septria Susanti (CV. Adiba Aisha Amira, 2025)
Measurement of the company's financial performance must be able to provide indicators of changes in the level of welfare of shareholders as a result of investment in a certain period of time. With the means of financial information as a tool of management accountability to company owners, depiction of the company's success sectors and as a consideration in decision making from the influence of capital structure and liquidity. This study aims to determine the effect of Capital Structure (Debt to Equty), Liquidity (Current Ratio) on Financial Performance (Return On Asset) in Basic Materials Sub-Sector Manufacturing Companies Listed on the IDX in 2019-2023. This type of research uses quantitative descriptive research methods which look for cause-and-effect relationships between variables or to test predetermined hypotheses with discussion of theories from experts. The research sample obtained was 120 observation data, using Purposive Sampling technique. The data analysis method used is descriptive statistical test, classicalassumption test, multiple linearregression test, hypothesistesting, coefficient ofdetermination (R2) test. The results of the research conducted show that capital structure has a negative and significant effect on financial performance in manufacturing companies in the basic materials sub-sector listed on the Indonesia Stock Exchange in 2019-2023. Liquidity also has a negative and significant effect on financial performance.